Functionalization of multi-walled carbon nanotubes with indazole. (1st March 2019) - Jurzinsky, Tilman; Gomez-Villa, Eduardo Daniel; Kübler, Markus; Bruns, Michael; Elsässer, Patrick; Melke, Julia; Scheiba, Frieder; Cremers, Carsten
Abstract: In this work, the functionalization of carbon nanotubes (CNTs) with indazole groups covalently bound to the CNTs' surface is reported. The novel material was structurally characterized via near edge X-ray absorption fine structure (NEXAFS) spectroscopy and X-ray photoelectron spectroscopy (XPS) and successful functionalization was proven. As the novel material is a potential candidate for catalyst support application in high-temperature proton-exchange membrane fuel cells (HT-PEMFCs), thermal and electrochemical stability of the novel material was investigated. Measurements via thermogravimetric analysis coupled to a mass spectrometer (TGA-MS) showed that the indazole-functionalized CNTs are thermally stable until a temperature of approx. 300 °C is reached. The thermal degradation of the functional group was tracked by monitoring the evolution of NOX gases. Furthermore, electrochemical stability of the novel material was evaluated using high-temperature differential electrochemical mass spectrometry (HT-DEMS) under gas-phase conditions. Compared to unmodified CNTs, it was shown that the functionalization leads to a slightly increased electrochemical carbon corrosion. However, the indazole-functionalized CNTs show a higher electrochemical stability than carbon black (Vulcan XC72R) typically used as catalyst support in HT-PEMFCs. In comparison to unmodified CNTs, functionality tests of the indazole-functionalized CNTs showed a better dispersibility in water and a lower contact angle with concentrated H3 PO4, which is the electrolyte in HT-PEMFCs. Ultimately, ion exchange capacity measurements showed that the indazole-functionalized CNTs are able to bind protons in the catalyst layer and, therefore, potentially improve the catalyst-electrolyte interface as well as the proton conductivity in the catalyst layer.